SOCIAL CONNECTEDNESS, GRATITUDE AND DEMOGRAPHIC VARIABLES AS PREDICTORS OF TEACHERS’ PERCEPTIONS OF ORGANIZATIONAL CYNICISM: PREDICTORS OF TEACHERS’ PERCEPTIONS OF ORGANIZATIONAL CYNICISM - Alanoglu, Müslim; Karabatak, Songül (International Online Journal of Education and Teaching, 2021)
This study aimed to test the predictive power of teachers’ social connectedness and gratitude levels and their demographic characteristics to predict their organizational cynicism perception. The study was designed in relational screening model. 304 teachers were reached from the population with snowball sampling method. Data were collected with Organizational Cynicism Scale, Social Connectedness Scale and Gratitude Scale. Correlation analysis and hierarchical regression were performed during the analyses. According to correlation analysis results, there were moderate and negative associations between organizational cynicism and social connectedness and gratitude, low and negative association between organizational cynicism and gender and low and positive associations between organizational cynicism and level of education and professional seniority. There were no significant association between organizational cynicism and marital status. As a result of this study, it was found that the independent variable which had the highest predictive value for organizational cynicism was social connectedness, followed by gratitude and the variable group with the lowest predictive value was found as demographic characteristics.